Asuhan Keperawatan pada Ny. S Post Operasi Laminektomi dengan Teknik Relaksasi Genggam Jari untuk Mengurangi Nyeri di Ruang Amarilis RSUD Prof. Dr. Margono Soekarjo Purwokerto - Salsabila, Hima Setya; Wirakhmi, Ikit Netra; Kusuma, Agus Kurniadi Hananta (Lembaga Pengembangan Kinerja Dosen, 2025)
Pain is one of the main complaints experienced by postoperative patients, including those undergoing laminectomy, which can interfere with comfort, hinder mobility, and slow the healing process. Non-pharmacological nursing interventions such as relaxation techniques have become important alternatives for reducing pain holistically. This study aims to evaluate the effectiveness of the finger-holding relaxation technique in reducing pain in postoperative laminectomy patients. The study used a descriptive case study design involving a patient named Mrs. S in the Amarilis Ward of Prof. Dr. Margono Soekarjo Regional Hospital, Purwokerto. The intervention was carried out for three consecutive days, twice a day, with each session lasting 15 minutes. The results showed a marked decrease in pain score from a scale of 7 (severe pain) on the first day to 1 (mild pain) on the fourth day, accompanied by gradual improvement in physical mobility, absence of surgical wound infection, and better discharge readiness. This technique also had a positive impact on the patient’s emotional comfort. Therefore, the finger-holding relaxation technique is proven to be a simple yet effective intervention in supporting the holistic recovery of postoperative laminectomy patients.